Cu1.5Mn1.5O4 spinel: a novel anode material for lithium-ion batteries. Issue 61 (10th June 2016) - Quan, Jingbin; Mei, Lin; Ma, Zheng; Huang, Jichun; Li, Decheng
Abstract : A facile spray drying method has been developed for the synthesis of Cu1.5 Mn1.5 O4, a novel material for lithium-ion batteries, which exhibits excellent cyclic retention. Abstract : Copper manganese oxide Cu1.5 Mn1.5 O4, a novel anode material for lithium-ion batteries, was synthesized via a spray drying method. SEM images demonstrated a strong dependence of the morphologies of secondary and primary particles on the synthesis parameters. The surface electronic states and chemical compositions of manganese and copper in the sample were confirmed by XPS. The electrochemical results demonstrated that the sample synthesized at an annealing temperature of 700 °C showed great cycling performance, and retained a specific capacity of 464 mA h g −1 at a current of 100 mA g −1 after 60 cycles.